UPAYA MENINGKATKAN MINAT BELAJAR FISIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SIKLUS (LEARNING CYCLE ”5E”) DI SMP NEGERI 1PANYABUNGAN - Darwis Darwis; Rizky Ariaji (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
The problem in this research is the low interest of physics student learning influence to the success of a process of physics learning. To overcome this problem, this research applied learning cycle model (Learning Cycle "5E"). This study aims to improve students' learning creativity, student learning activities, teachers' ability to manage learning and students' interest in physical learning through learning cycle model (Learning Cycle "5E") on Cubes and Balok subjects in class VIII-2 SMP Negeri 4 Angkola Timur. Data analysis shows that for the cycle I there is increase cycle II. The result of observation of student activity on cycle I obtained by cycle II increase. Observation on the ability of teachers to manage to learn in cycle I am in the category of "good," and for cycle II there is an increase that is in the category of "very good". The above conclusions suggest that the implementation of the learning cycle model (Learning Cycle "5E") can be used in an effort to increase the students' learning interest in physics and to the teacher, it is expected to implement the learning cycle model (Learning Cycle "5E") on other subjects on physics lessons or appropriate subjects. Keywords: Student Learning Interest, Learning Cycle Model "5e".